2019
DOI: 10.1371/journal.pone.0218411
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microbleeds are not associated with postoperative delirium and postoperative cognitive dysfunction in older individuals

Abstract: Background Cerebral microbleeds (CMB) occur in the context of cerebral small vessel disease. Other brain MRI markers of cerebral small vessel disease are associated with the occurrence of postoperative delirium (POD) and postoperative cognitive dysfunction (POCD), but for CMB this is unknown. We aimed to study the association between CMB and the occurrence of POD and POCD in older individuals. Methods The current study consists of 65 patients (72±5 years) from the BIOCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Studies investigating the relation between intraoperative hyperglycemia and cerebral markers on MRI are scarce. In our previous study, we found no association between intraoperative hyperglycemia and pre-to postoperative volume changes of the hippocampus and the hippocampal subfields, the frontal lobe, and frontal cortical thickness [14]. To the best of our knowledge no previous studies have focused on the association between intraoperative hyperglycemia and cerebrovascular markers.…”
Section: Introductionmentioning
confidence: 76%
“…Studies investigating the relation between intraoperative hyperglycemia and cerebral markers on MRI are scarce. In our previous study, we found no association between intraoperative hyperglycemia and pre-to postoperative volume changes of the hippocampus and the hippocampal subfields, the frontal lobe, and frontal cortical thickness [14]. To the best of our knowledge no previous studies have focused on the association between intraoperative hyperglycemia and cerebrovascular markers.…”
Section: Introductionmentioning
confidence: 76%
“…Although a few studies have investigated brain CSVD markers (e.g., WMH and cerebral microbleeds) in relation to delirium ( Omiya et al, 2015 ; Nitchingham et al, 2018 ; Lachmann et al, 2019 ; Clancy et al, 2021 ; Pendlebury et al, 2022 ), no previous study has yet explored the link between MRI-visible PVS and delirium. PVS is frequently seen in the aging brain ( Bown et al, 2022 ) and has been proposed as a key contributor to cognitive decline and dementia in older adults ( Debette et al, 2019 ; Paradise et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, POCD according to ISPOCD criteria after three months was the defined endpoint of the BioCog study and assessed in the designated POCDr package for R (Moller et al, 1998;Spies et al, 2021). Since the incidence of POCD in the sample presented here was very low (Lachmann et al 2019), we decided to analyze the association of SWI hypointensities with a continuously scaled parameter for global cognitive function. Therefore, we calculated the global cognitive component 'g' to assess cognitive decline after surgery as described in previous publications (Feinkohl et al, 2019;Feinkohl, Janke, et al, 2020;Lammers et al, 2018).…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…Susceptibility weighted imaging (SWI) has previously been used to study increased iron deposition and calcification in aging (Harder et al, 2008) and conditions such as Parkinson’s disease (Meijer et al, 2015; Schneider et al, 2016). In a previous work, we studied cerebral microbleeds in POD using SWI (Lachmann et al, 2019). Although the work did not find evidence for an association of microhemorrhages with a predisposition for POD, it is unknown if iron deposits or calcification from other sources with distinct distribution patterns, e.g., metal-binding protein aggregates or accumulation in microglia, could contribute to POD development.…”
Section: Introductionmentioning
confidence: 99%